Hodgkin's Lymphoma in an elite endurance athlete - Schumacher, Y. O.; Muser, K.; Hirschberger, B.; Roecker, K.; Dickhuth, H. H.; Pottgiesser, T. (Medicine & Science in Sports & Exercise, 2008)
Cancer is a life-threatening condition. We describe the case of a 22-yr-old world-class endurance athlete who presented with mild local lymphadenopathy but without any systemic complaints or impaired performance. He was subsequently diagnosed with stage III A (S) Hodgkin's lymphoma. A complete physiological workup before the diagnosis revealed high aerobic capacity. Immediately after six courses of escalated BEACOPP chemotherapy in an identical test setting, aerobic capacity was markedly reduced (-42%), mainly because of a decrease in total hemoglobin mass (-37%), despite maintaining a certain amount of endurance training. Other potentially performance-limiting systems such as heart, lung, or aerobic metabolism did not show any signs of impairment. Two months after chemotherapy, the athlete had recovered his hemoglobin mass, and his aerobic performance was almost back to pretherapy levels. This case illustrates that advanced malignancies can be present in elite athletes without affecting performance, and that aerobic capacity can be regained within a short time after systemic chemotherapy.